IMPLEMENTASI STRATEGI PEMBELAJARAN “CEGERA” BERBASIS PRODUK PADA MAHASISWA PGPAUD FKIP UNIVERSITAS MUHAMMADIYAH PURWOKERTO - Okto Wijayanti (Khazanah Pendidikan, 2016)
This study aims to determine the implementation of learning strategies "Cegera" Product-based dance works (motion tracks) on a course 4th semester student art PGPAUD FKIP UMP. The study population amounted to 6 students. The method used in this research carried out by three stages: plan, do, and see Collecting data using three data collection techniques. Data collection techniques used were interviews, observation and documentation methods. Analysis of the data used is descriptive qualitative. The results of this study were (1) Implementation of a learning strategy "Cegera" consists of three steps namely storytelling strategy implementation, expression and movement songs. (2) makes the students active, mutual cooperation, tolerance, taggung responsibility in the learning process. (3) The implementation process of learning strategies is emphasized by the terms enjoyable, fun and relaxed so as to enable the students are free to express ideas, concepts, exchange opinions, to think together, explore and explore. (4) Product dance works produced memalui learning implementation "Cegera" successfully presented well in the final practice exam semester. Keywords: learning strategies, “Cegera”, and Artistic Dance